STUDENT DIFFICULTY ANALYSIS IN COMPLETING CHEMISTRY ODD SEMESTER EXAM - Mujakir Mujakir; Haris Munandar; Nur Fitri Hidayati (Jurnal Tadris Kimiya, 2020)
The problems obtained by the researcher in Senior High School 5 Takengon Central Aceh show that most students have difficulty solving odd semester exam questions in chemistry learning. This study aims to determine what difficulties students face and what factors cause students to have difficulties. The method used in this research is descriptive method with a qualitative approach. Data were collected through tests, questionnaires, and interviews. Data were analyzed descriptively and qualitatively. The results obtained indicate that students have difficulty in chemical calculations, exothermic and endothermic reactions, and the concept of chemistry equilibrium; the factors that affect students' difficulties in solving odd semester final exam questions on chemistry are the students', physical condition, students' motivation, and interest and students' low mathematical abilities.